USE OF IRRIGATING SOLUTIONS IN PULPECTOMY OF DECIDUOUSTEETH: LITERATURE REVIEW - Jessica Cristina Dalcin Manfio; Patricia Kolling Marquezan; Flávia Kolling Marquezan (Portal de Periódicos da Marinha do Brasil, 2021)
Cleaning of root canals is a crucial step for a successful endodontic treatment. For this reason, the search for effective irrigating solutions in endodontic therapy of deciduous teeth is frequent in research and it demonstrates the need to find substances with lower toxicity and greater efficiency. Thus, this study aims to analyze the different irrigating solutions and protocols in the endodontic treatment of deciduous teeth, in order to build a clinical approach. For this, a literature search was performed in the Databases PubMed/MEDLINE, Cochrane Library, SCIELO, Portal de Periódicos CAPES and VHL using the combination of the terms "deciduous tooth," "root canal irrigants," "pulpectomy" and their derivatives, associated with each other by the Boolean operator "AND" and adapted for each database. The searches were carried out from July to August 2020. In total, 192 results were found. After a critical reading, eight studies were selected. The review included studies addressing the most common irrigating solutions: sodium hypochlorite, chlorhexidine digluconate, citric acid, and ethylenediaminetetraacetic acid (EDTA) in endodontic therapy of deciduous teeth. EDTA and chlorhexidine digluconate have low toxicity and the 1% sodium hypochlorite combined with 6% citric acid have the most prosperous combination. The association of these two substances proved to be more efficient in cleaning root canals and removing the smear layer. However, more studies are necessary, mainly clinical ones, to confirm the best irrigating protocol for the endodontic treatment of deciduous teeth.